Evaluation of heart rate recovery in relation to playing position in professional soccer players - Bonaiuto, M.; Di Mauro, D.; Speciale, F.; Pagano, F.; Buda, D.; Vita, G.; Magaudda, L.; Trimarchi, F. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: The aim of the study was the evaluation of the autonomic cardiac function in professional soccer players by heart rate recovery (HRR) measurement after 1` or 2` of active recovery (HRR1 or HRR2, respectively) from an exercise stress test. METHODS: Ninety-two adult professional soccer players (aged 25.27 ± 4.06 years). The exercise test was performed using a cycle ergometer with a ramp protocol. The subjects began with a load of 25W that was increased by 3W every 6 seconds, followed by an active recovery phase. We assessed the heart rate at rest (HRr), the PR interval, the QT and QTc intervals, the QRS axis, the QRS duration, the maximal heart rate, and the heart rate and heart rate recovery after 1 or 2 minutes from suspension of the load. RESULTS: The HRR1 was significantly slower (20.53 SD 6.67) among goalkeepers in comparison with other roles (HRR1 30.7 SD 6.62) CONCLUSION: These data show better autonomic function in roles with alternate aerobic-anaerobic activity compared to other roles. The results agree with the data in other literature about the positive action of intense aerobic-anaerobic physical activity on cardiovascular autonomic system adjustment.